The prosody of Shingazidja relatives - Patin, Cédric (ZAS Papers in Linguistics, 2010)
Símákonde is an Eastern Bantu language (P23) spoken by immigrant Mozambican communities in Zanzibar and on the Tanzanian mainland. Like other Makonde dialects and other Eastern and Southern Bantu languages (Hyman 2009), it has lost the historical Proto-Bantu vowel length contrast and now has a regular phrase-final stress rule, which causes a predictable bimoraic lengthening of the penultimate syllable of every Prosodic Phrase. The study of the prosody / syntax interface in Símákonde Relative Clauses requires to take into account the following elements: the relationship between the head and the relative verb, the conjoint / disjoint verbal distinction and the various phrasing patterns of Noun Phrases. Within Símákonde noun phrases, depending on the nature of the modifier, three different phrasing situations are observed: a modifier or modifiers may (i) be required to phrase with the head noun, (ii) be required to phrase separately, or (iii) optionally phrase with the head noun.